Analisa Perbandingan Hasil Terjemahan Google Translate dan U Dictionary Dalam Lirik Lagu To The Bone oleh Pamungkas - Arif, Hana Putri (CV Insan Kreasi Media, 2024)
Digital translation tools such as Google Translate and U-Dictionary were created to make it easier to translate each language. However, not all of these services have accurate translation results. So therefore, the aim of this research is to see a comparison of the accuracy of Google Translate and U-Dictionary translation results in translating the lyrics of the song To The Bone by Pamungkas in order to understand the meaning of the song correctly. The analytical method used is a descriptive qualitative literature study with the instrument used, namely the lyrics of the song To The Bone by Pamungkas. The research results show that the U-Dictionary translation results have a number of accurate sentence translation results. That is one sentence higher than the Google Translate translation results. U-Dictionary and Google Translate still have many shortcomings and errors in translating sentences. However, it can still be used as an alternative to help with the translation process. Note that users need to re-check the translation results to match the context again to check their suitability.